Clinical outcomes of operative repair of complete rupture of the proximal interphalangeal joint collateral ligament: Comparison with non-operative treatment - Seoung Joon Lee; Jun Hee Lee; In Cheul Hwang; Joon Kuk Kim; Jung Il Lee (Acta Orthopaedica et Traumatologica Turcica, 2017)
Objectives: The purpose of this study was to compare the outcomes of non-operative treatment and operative repair of grade III injuries with complete rupture of the collateral ligament of the proximal interphalangeal (PIP) joint. Patients and methods: Seventeen patients with grade III injuries with at least 6 months of follow-up were included. Seven patients underwent non-operative treatment and 10 patients underwent operative treatment. We evaluated the following clinical outcomes after treatment: 1) range of motion of the PIP and distal interphalangeal (DIP) joints, 2) joint stability, 3) pain score, and 4) amount of fusiform deformity of the PIP joint. Results: There was no instability in the lateral stress test in either group. The ranges of motion of the PIP and DIP joints were not statistically different between the two groups at final follow-up. However, the ranges of motion recovered more quickly in the operative group than the non-operative group within the first 3 months after treatment. Patients in the operative group had less pain and better cosmetic appearance of the PIP joint. Conclusion: Our results suggest that operative repair of the PIP collateral ligament can provide good joint stability, rapid functional recovery, and minimize fusiform deformity of the PIP joint. Level of evidence: Level III, Therapeutic study. Keywords: Proximal interphalangeal joint, dislocation, PIP collateral ligament, Surgical repair, Suture anchor